PEMBUATAN DAN PENGUJIAN SENSOR ULTRASONIK SEBAGAI FEEDBACK PADA SISTEM KENDALI OTOMATIK PITCH ATTITUDE HOLD - U. M Zaeny; T Indriyanto; H Muhammad (Mesin, 2007)
Standard altimeter, i.e. static tube, does not work accurate enough for vehicle flying several meters from the ground. One alternative for measuring altitude in this case is using ultrasonic range-meter. This idea is brought further by using two range-meters to measure pitch attitude. Laboratory experiments were conducted to study this idea statically by constructing them in an inclined moving bar and dynamically by arranging them in a Pitch Attitude Hold control system.